Electrical and electronic waste collection by private company in Bandaraya Kota Kinabalu Sabah - Molia Sebi Dinggai; Mohammad Tahir Mapa; Fionna George (Fakulti Kemanusiaan Seni dan Warisan, UMS, 2019)
Electrical and electronic waste (e-waste) management has become a global concern, therefore, e-waste management requires all stakeholders such as the government, private sectors, non-governmental organisations (NGOs), informal sector and communities to effectively coordinate their efforts to manage it. However, in Malaysia, the management of e-waste has yet to integrate all parties concerned, especially in the private sector. Therefore, this study aims to observe the management of e-waste by a private company in the West Coast of Sabah. The objective of this study is to identify the types of e-waste collected by selected private companies as well as the e-waste management processes undertaken by the selected companies. This study uses two research methods: unstructured interviews and surveys. The findings show that there are four private companies actively involved in collecting e-waste from government offices, public sector agencies, schools, universities, as well as other corporate houses. The four companies stated are Multihope’s private limited company, GNC Recycle’s private limited company, SMAPO’s private limited company, and Berusaha Jaya Trading company. The items collected by the private companies are desktop computers, laptops, televisions, mobile phones, radio/mp3, printers, refrigerators, washing machines, air conditioning, fluorescent lamps, car batteries, fans, and electric rice cookers. Next, each of the four companies has its system for managing e-waste. In conclusion, this study shows that there are still weaknesses in e-waste management in the private sector in the city of Kota Kinabalu. This study is expected to assist the private sector, the Kota Kinabalu City Hall and the Department of Environment as the official agency that manages e-waste so that the information collected in this study can be used to develop the appropriate policies or methods for e-waste management in residential areas. A holistic approach is required to manage e-waste, whether it be to dispose or recycle e-waste in a sustainable way to save the environment and human health.